Coupled effects of hydrophobic layer and vibration on thermal efficiency of two-phase closed thermosyphons. Issue 14 (19th February 2015) - Tong, Wei Li; Tan, Ming K.; Chin, Jit Kai; Ong, K. S.; Hung, Yew Mun
<x xml:space="preserve">Abstract</x> Observation of elongated liquid jets and entrained droplets from the liquid–vapor interface induced by high-acceleration vibration provides valuable insights into the physical process of liquid–vapor interaction phenomena in a thermosyphon (TPCT).